2010
DOI: 10.1042/bst0380488
|View full text |Cite
|
Sign up to set email alerts
|

Presynaptic dysfunction in Huntington's disease

Abstract: HD (Huntington's disease) is produced by the expression of mutant forms of the protein htt (huntingtin) containing a pathologically expanded poly-glutamine repeat. For unknown reasons, in HD patients and HD mouse models, neurons from the striatum and cerebral cortex degenerate and lead to motor dysfunction and dementia. Synaptic transmission in those neurons becomes progressively altered during the course of the disease. However, the relationship between synaptic dysfunction and neurodegeneration in HD is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
17
1

Year Published

2011
2011
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 24 publications
(18 citation statements)
references
References 51 publications
0
17
1
Order By: Relevance
“…Synaptic damage has been extensively reported in neurodegenerative diseases, including Alzheimer’s [111114,116,117] Parkinson’s [118122] and Huntington’s [2223,123127]. However, the precise factors that cause synaptic degeneration are not completely understood.…”
Section: Synaptic Damage In Huntington’s Diseasementioning
confidence: 99%
“…Synaptic damage has been extensively reported in neurodegenerative diseases, including Alzheimer’s [111114,116,117] Parkinson’s [118122] and Huntington’s [2223,123127]. However, the precise factors that cause synaptic degeneration are not completely understood.…”
Section: Synaptic Damage In Huntington’s Diseasementioning
confidence: 99%
“…2009; Lu, 2009; Cepeda et al . 2010; Rozas et al . 2010) have offered opportunities to illuminate the possible links between altered transmitter signalling and neurotoxicity and to assess more subtle modifications in cellular interactions prior to neurodegeneration (see, for example, Milnerwood et al .…”
Section: Introductionmentioning
confidence: 99%
“…1 D). In contrast, Romero et al (2008) reported elevated resting synaptic Ca 2ϩ levels at the 128Qhtt FL strain with no changes in the frequency of spontaneous release (for review, see Rozas et al, 2010). We nevertheless recorded a higher MEPP frequency in R6/1 junctions after high-frequency stimulation trains, but we cannot distinguish whether such an increase is due to (1) abnormally high cytosolic [Ca 2ϩ ], (2) an effect downstream of a Ca 2ϩ -dependent step of exocytosis activation, or (3) both.…”
Section: Alterations In Camentioning
confidence: 99%
“…Although htt is ubiquitously expressed in neuronal and non-neuronal cells, the most vulnerable neurons in HD are the striatal medium spiny neurons and the cortical pyramidal neurons. Likely, mutant-htt becomes toxic through multiple molecular mechanisms, including synaptic dysfunction (Smith et al, 2005;Rozas et al, 2010). Detailed studies of synaptic alterations in HD mouse models in the brain regions that typically degenerated in HD have reported different phenotypes depending on synaptic type, brain region, and level of degeneration (Zeron et al, 2002;Cepeda et al, 2003Cepeda et al, , 2007Smith et al, 2005;Cummings et al, 2009;Rozas et al, 2010).…”
Section: Introductionmentioning
confidence: 99%